Ice Cold Killers - The Rituals of Murderers - History, World (Saga Egmont, 2021)
From singling out victims at bus stops, targeting women with long, blonde hair, saving trophies, or dismembering and even eating their victims, each serial killer set a unique ritual for their murder, and these rituals are what betrays them in the end. Serial killers often begin with a few unplanned murders, where they experiment with which actions give them the greatest release.Moving on they start to carefully select their victims, either by stalking them or staking out special locations where their victim – such as prostitute or child – can be found alone.But after a while the killer's hunt for satisfaction makes him overconfident.Follow on the heels of the police in their hunt for four relentless serial killers. These stories contain gruesome details and are not suitable for children.-